The Dark Side of Investor Conferences: Evidence of Managerial Opportunism - Bushee, Brian J.; Taylor, Daniel J.; Zhu, Christina (The Accounting Review, 2023)
ABSTRACT Although the shareholder benefits of investor conferences are well-documented, evidence on whether these conferences facilitate managerial opportunism is scarce. We examine whether managers opportunistically exploit heightened attention around the conference to “hype” the stock. We find that (1) managers increase the quantity of voluntary disclosure leading up to the conference, (2) these disclosures are more positive in tone and increase prices to a greater extent than post-conference disclosures, and (3) these disclosures are more pronounced when insiders sell their shares immediately prior to the conference. In circumstances where pre-conference disclosures coincide with pre-conference insider net selling, we find evidence of a significant return reversal––large positive returns before the conference and large negative returns after the conference––and that the firm is more likely to be named in a securities class action lawsuit. Collectively, our findings are consistent with some managers hyping the stock prior to the conference.